ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH PADA NIAT BERWIRAUSAHA (STUDI KASUS PADA MAHASISWA FAKULTAS EKONOMI DI KOTA MEDAN - Winarto Winarto; Jon Henri Purba (Universitas Methodist Indonesia, 2019)
Higher education has an important role in educating and motivating students to be entrepreneurs. The research aims to analyze the role of entrepreneurship education, attitude toward entrepreneurship, subjective norm, perceived behavioral control, and proactive personality on entrepreneurship intentions. This research was conducted among Faculty of Economics students in Medan, North Sumatera. The research used a quantitative descriptive method by using a questionnaire, which has been filled out by the students, employing convenience sampling. The results show that all the examined variables influenced the entrepreneurship intentions among students. Theoretical and practical implications will be explored at the end of the paper.